Developing a COVID-19 mortality risk prediction model when individual-level data are not available - Noam Barda (Nature Portfolio, 2020)
Identification of individuals at risk of severe COVID-19 disease could inform treatment and public health planning. Here, the authors develop and validate a risk prediction model for COVID-19 mortality in Israel by building a model for severe respiratory infection and recalibrating it using COVID-19 case fatality rates.